Hrvatsko-mađarske leksikografske veze između 1990.–2020. godine - BOCKOVAC, TIMEA (SlavVaria, 2021)
Croatian-Hungarian dictionaries that have been published in Hungary and Croatia between 1990 and 2020. This paper showcases Croatian-Hungarian dictionaries that have been published in Hungary and Croatia between 1990 and 2020. In the line of publications examples of descriptive, prescriptive, normative, thematic dictionaries and glossaries are found. Monolingual and bilingual dictionaries, subject, dialectology, field-specific and terminology dictionaries are thematized and categorized synchronically and diachronically, furthermore, they are analyzed according to notion and meaning criteria and the structure of their entries and lemmas. The matter of e-lexicography and the digitalization of existing physical editions is discussed in tandem with the belonging of the field of lexicology in the education process and the modern curriculum.